A double-blind, randomized, placebo-controlled trial of combined calcitriol and ergocalciferol versus ergocalciferol alone in chronic kidney disease with proteinuria. Issue 1 (December 2017) - Susantitaphong, Paweena; Nakwan, Siriwan; Peerapornratana, Sadudee; Tiranathanagul, Khajohn; Katavetin, Pisut; Srisawat, Nattachai; Praditpornsilpa, Kearkiat; Eiam-Ong, Somchai
Abstract Background KDOQI guideline suggests that nutritional vitamin D should be supplemented in chronic kidney disease (CKD) patients who have vitamin D insufficiency/deficiency. However, there are scarce data regarding the additional benefit of active vitamin D supplement in CKD patients who were receiving nutritional vitamin D supplement. This study was conducted to explore the effect of adding active vitamin D to nutritional vitamin D supplement on proteinuria and kidney function in CKD with vitamin D insufficiency/deficiency. Methods This double-blind, randomized placebo-controlled trial was performed to answer the above question. Sixty-eight patients with CKD stage 3–4, urine protein to creatinine ratio (UPCR) > 1 g/g, and serum 25OH-D level < 30 ng/mL were enrolled. Patients were randomly assigned to receive 12-week treatment with oral ergocalciferol plus placebo (n  = 36) or oral ergocalciferol plus calcitriol (n  = 32). Results The mean baseline values of UPCR of both groups were comparable (3.6 ± 3.8 g/g in combined group and 3.5 ± 3.0 g/g in ergocalciferol group). Following 12-week treatment, there were significant reductions in UPCR from baseline in both groups (2.3 ± 2.1 g/g in combined group and 2.4 ± 2.0 g/g in ergocalciferol group). The percentage reductions in UPCR of both groups were not significantly different. The mean eGFR and blood pressure did not differ between baseline and 12-week follow-up and between both groups. No severe hypercalcemia or serious side effects were noted in both groups. Conclusions The proteinuria lowering effect of ergocalciferol in CKD patients with vitamin D deficiency was demonstrated. Additional calcitriol supplement did not have more effects on proteinuria. Trial registration (Thai Clinical Trials Registry (TCTR)20140929002 ). Date of registration: September 27, 2014.